2015
DOI: 10.1002/cmdc.201500301
|View full text |Cite
|
Sign up to set email alerts
|

Development of Small‐Molecule Trypanosoma brucei N‐Myristoyltransferase Inhibitors: Discovery and Optimisation of a Novel Binding Mode

Abstract: The enzyme N-myristoyltransferase (NMT) from Trypanosoma brucei has been validated both chemically and biologically as a potential drug target for human African trypanosomiasis. We previously reported the development of some very potent compounds based around a pyrazole sulfonamide series, derived from a high-throughput screen. Herein we describe work around thiazolidinone and benzomorpholine scaffolds that were also identified in the screen. An X-ray crystal structure of the thiazolidinone hit in Leishmania m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 19 publications
0
18
1
Order By: Relevance
“…25 The efforts of organizations like the DNDi and Tres Cantos Open Lab Foundation have increased awareness about neglected parasitic diseases, and inspired many new trypanosomiasis drug discovery programs. Most campaigns have focused on either T. brucei 13,[26][27][28][29][30][31][32][33][34][35][36] or T. cruzi; [37][38][39][40][41][42] fewer have involved a concerted effort to discover leads that are effective against both pathogenic species, [43][44][45][46][47][48][49][50][51][52][53] despite the economies of broad-spectrum drug development, especially for neglected diseases.…”
Section: Introductionmentioning
confidence: 99%
“…25 The efforts of organizations like the DNDi and Tres Cantos Open Lab Foundation have increased awareness about neglected parasitic diseases, and inspired many new trypanosomiasis drug discovery programs. Most campaigns have focused on either T. brucei 13,[26][27][28][29][30][31][32][33][34][35][36] or T. cruzi; [37][38][39][40][41][42] fewer have involved a concerted effort to discover leads that are effective against both pathogenic species, [43][44][45][46][47][48][49][50][51][52][53] despite the economies of broad-spectrum drug development, especially for neglected diseases.…”
Section: Introductionmentioning
confidence: 99%
“…Target based screening has also become an important approach used in antitrypanosomal research with inhibitors of a range of different targets being reported. Some of these include inhibitors of trypanothione reductase, rhodesain, tryparedoxin, GSK3, N‐myristoyl transferase, trypanothione synthetase, ornithine decarboxylase, and phosphofructokinase . Many compounds from a broad range of structural classes have also been identified through more traditional phenotypic screening approaches, including pyridine based compounds, adamantanes, quinones and quinolones, and pyrimidines .…”
Section: Introductionmentioning
confidence: 99%
“…The resulting peptidomimetic is characterized by sub-micromolar potency against both enzymes and marginal selectivity over HsNMT. Interestingly, 20% of the electron density of the inhibitor-NMT complex structure corresponds to an N-myristoylated inhibitor product and the CoA by-product, providing the first direct structural evidence for a product complex in NMT (Brand et al 2014;Spinks et al 2015). (B) Superpositions of the crystal structures of DDD85646 (19) (PDB code: 2WSA, red) with, respectively, lead compounds of the thiazolidinone (21) (PDB code: 5AG6, green) and benzomorpholinone (22) (PDB code: 5AGE, blue) series in complex with the TbNMT surrogate LmNMT reveal that the two new inhibitor classes (21 and 22) exhibit a different binding mode than the sulphonamides (19) (Spinks et al 2015).…”
Section: Plasmodium and Leishmaniamentioning
confidence: 93%
“…10. (A) Biological activity against Tb NMT and Hs NMT1, antiparasitic cell activity against BSF T. brucei parasites, and BBB permeability (B:B = brain-to-blood ratio, ND = not determined) of Tb NMT lead inhibitors (Brand et al 2014; Spinks et al 2015). (B) Superpositions of the crystal structures of DDD85646 ( 19 ) (PDB code: 2WSA, red) with, respectively, lead compounds of the thiazolidinone ( 21 ) (PDB code: 5AG6, green) and benzomorpholinone ( 22 ) (PDB code: 5AGE, blue) series in complex with the Tb NMT surrogate Lm NMT reveal that the two new inhibitor classes ( 21 and 22 ) exhibit a different binding mode than the sulphonamides ( 19 ) (Spinks et al 2015). …”
Section: Inhibitors Of Protein Lipidation In Protozoan Parasitesmentioning
confidence: 99%